Evolution of right and left ventricle routine and speckle-tracking echocardiography in patients recovering from coronavirus disease 2019: a longitudinal study. (20th September 2021) - Baruch, Guy; Rothschild, Ehud; Sadon, Sapir; Szekely, Yishay; Lichter, Yael; Kaplan, Alon; Taieb, Philippe; Banai, Ariel; Hochstadt, Aviram; Merdler, Ilan; Arbel, Yaron; Laufer-Perl, Michal; et al.
Abstract: Aims: We aim to assess changes in routine echocardiographic and longitudinal strain parameters in patients recovering from Coronavirus disease 2019 during hospitalization and at 3-month follow-up. Methods and results: Routine comprehensive echocardiography and STE of both ventricles were performed during hospitalization for acute coronavirus disease 2019 (COVID-19) infection as part of a prospective pre-designed protocol and compared with echocardiography performed ∼3 months after recovery in 80 patients, using a similar protocol. Significantly improved right ventricle (RV) fractional area change, longer pulmonary acceleration time, lower right atrial pressure, and smaller RV end-diastolic and end-systolic area were observed at the recovery assessment ( P < 0.05 for all). RV global longitudinal strain improved at the follow-up evaluation (23.2 ± 5 vs. 21.7 ± 4, P = 0.03), mostly due to improvement in septal segments. Only eight (10%) patients recovering from COVID-19 infection had abnormal ejection fraction (EF) at follow-up. However, LV related routine ( E, E / e ′, stroke volume, LV size), or STE parameters did not change significantly from the assessment during hospitalization. A significant proportion [36 (45%)] of patients had some deterioration of longitudinal strain at follow-up, and 20 patients (25%) still had abnormal LV STE ∼3 months after COVID-19 acute infection. Conclusion: In patients previously discharged from hospitalization due to COVID-19 infection, RV routine echocardiographic and RV STE parameters improve significantly concurrently with improved RV haemodynamics. In contrast, a quarter of patients still have LV systolic dysfunction based on STE cut-offs. Moreover, LV STE does not improve significantly, implying subclinical LV dysfunction may be part and parcel of recovering from COVID-19 infection. Graphical Abstract: